Strategic orientations, marketing capabilities and innovativeness: an adaptive approach - Akgun, Ali E.; Polat, Volkan (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose This study aims to investigate marketing capabilities that represent the marketing mix from an adaptive perspective: brand management, customer relationship management, price management and multi-channel management. Also, this study identifies how adaptive marketing capabilities (AMCs) enrich superior innovativeness and speed-to-market regarding innovation orientation and marketing orientation as the two critical functions. Design/methodology/approach A questionnaire-based research was performed to test the proposed hypotheses. The data were collected from predominately marketing or research and development managers/senior specialists in 247 firms. Findings Strategic orientations that cover market and innovation orientation facilitate a firm's AMCs, positively affecting its innovativeness and speed-to-market. Also, AMCs mediate the relationship between strategic orientations, and innovativeness, and speed-to-market. Further, this study confirms the complementary association of AMC-related variables in enhancing firm innovativeness and speed-to-market. Research limitations/implications This study is subject to the limitations inherent in survey design, particularly convenient sampling and single informants. Originality/value This study broadens understanding of dynamic capabilities theory by examining how marketing capabilities can be enhanced and examined from an adaptive perspective for firms. This study also presents a model for the potential relationships among strategic orientations, AMCs, innovativeness and speed-to-market.
Keywords: Marketing strategy; Innovation; Adaptability; Dynamic capabilities; Strategic orientations; Marketing capability; SUPPLY CHAIN; SOCIAL CRM; E-COMMERCE; PERFORMANCE; IMPACT; INTEGRATION; ANTECEDENTS; RESOURCES; Business & Economics